2022
DOI: 10.1108/ijmf-10-2021-0501
|View full text |Cite
|
Sign up to set email alerts
|

Whether corporate green bonds act as armour during crises? Evidence from a natural experiment

Abstract: PurposeThe present study examines the rationale behind the increased global presence of corporate green bonds as a green financing tool to facilitate sustainable practices and eco-friendly investing. The authors investigate the intriguing question of whether the companies that issue green bonds are valued more by investors or not, and further extend our analysis by exploring whether the green image of companies helps to minimize the value erosion during a crisis and enhance the resilience of the stocks?Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Al Mamun et al (2022) demonstrate the positive effect of green finance on decarbonization, while Boubaker et al (2022b) highlight the resilience-enhancing role of corporate social responsibility practices during the COVID-19 pandemic. Finally, Sisodia et al (2022) find that green bond firms are valued higher by investors compared to brown bond firms, signaling their environmental commitment. Similarly, Alharbi et al (2023) underscore the significance of green finance, particularly green bonds, in fostering renewable energy production, and emphasize the importance of technological capacity and policy commitments in driving this impact.…”
Section: Introductionmentioning
confidence: 86%
“…Al Mamun et al (2022) demonstrate the positive effect of green finance on decarbonization, while Boubaker et al (2022b) highlight the resilience-enhancing role of corporate social responsibility practices during the COVID-19 pandemic. Finally, Sisodia et al (2022) find that green bond firms are valued higher by investors compared to brown bond firms, signaling their environmental commitment. Similarly, Alharbi et al (2023) underscore the significance of green finance, particularly green bonds, in fostering renewable energy production, and emphasize the importance of technological capacity and policy commitments in driving this impact.…”
Section: Introductionmentioning
confidence: 86%
“…Such findings, however, are not yet conclusive. Indeed, other studies did not find higher levels of resilience in companies that issue green bonds, compared to the brown ones, during the COVID‐19 crisis, despite reporting a lower value erosion (Sisodia et al, 2022). Bax et al (2023) showed that, during the COVID‐19 outbreak, the systemic risk reacted more readily to the idiosyncratic shocks of those companies having a greater rating in terms of environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In line with the above arguments, several papers argue that by issuing green bonds companies can signal their commitment to climate-friendly policies, making them attractive for investors who aim at contributing to reducing climate change risks (Kuchin et al, 2019;Daubanes et al, 2021;Flammer, 2021;Sisodia et al, 2022). These papers analyze the signaling effect by looking at how the stock market responds to the issuance of green bonds.…”
Section: Determinants Of Issuing Corporate Green Bondsmentioning
confidence: 96%